1996
DOI: 10.1097/00005392-199606000-00084
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Approaches to the Prognostic Stratification of Mild to Moderate Primary Vesicoureteral Reflux in Children

Abstract: Performance of staging voiding cystourethrography exclusively in children with renal scarring on a DMSA scan resulted in predictive accuracy that was close to what was achieved by performing voiding cystourethrography in all children with a urinary tract infection. To be able to limit cystourethrography to a select population could prove to be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…The prevalence of VUR in children with UTI varies among different racial groups. Studies in the USA, the UK, and Italy showed the highest prevalence of VUR (41-63%) [3][4][5]. The lowest reported prevalence of VUR in children with UTI was in Black American children (6-12%) and in Jamaican children (10%) [6,7].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The prevalence of VUR in children with UTI varies among different racial groups. Studies in the USA, the UK, and Italy showed the highest prevalence of VUR (41-63%) [3][4][5]. The lowest reported prevalence of VUR in children with UTI was in Black American children (6-12%) and in Jamaican children (10%) [6,7].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that radiological abnormalities exist in as many as 25-55% of children after their first UTI, with one-third having VUR [4][5][6][7][8][9][10]. There was a high incidence of acute pyelonephritis (APN) in the presence of VUR, but APN does not necessarily need VUR for its development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the United States, United Kingdom, and Italy showed the highest prevalence of VUR (41%-63%) [3,9,10]. In other countries with a predominately Caucasian population (Sweden and Australia), the prevalence is lower (24%-27%) [11,12].…”
Section: Discussionmentioning
confidence: 96%
“…UU., el Reino Unido e Italia, y las tasas más bajas varían entre el 6% y el 12% en los niños afroamericanos y son del 10% en los niños jamaiquinos. 3,[11][12][13][14] En nuestro país, en un estudio con 300 pacientes, Yılmaz y col. determinaron que la tasa de RVU era del 30,9%. 15 En el estudio actual, se observó que la tasa de RVU coincidía con la bibliografía relevante y que era estadísticamente significativa cuando se analizaron los grupos por separado.…”
Section: Discussionunclassified